PERSPEKTIF FILSAFAT PENDIDIKAN TERHADAP IMPLEMENTASI KURIKULUM MERDEKA - Narsan, Zhalfariani; Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to discuss the perspectives of educational philosophy on the implementation of the Independent Curriculum as a new paradigm in the Indonesian education system. This study was conducted to understand how various schools of educational philosophy provide a conceptual foundation for the principle of independent learning. The research method used is a literature review by analyzing various scientific sources discussing educational philosophy, learning practices, and the policies of the Independent Curriculum. The results show that educational philosophy plays an important role in shaping the direction, goals, and methods of learning. Various schools of educational philosophy contribute to directing education towards student-centered, relevant, and contextual learning. The implementation of the Independent Curriculum reflects the values ​​of humanism, existentialism, constructivism, and progressivism that emphasize freedom, responsibility, and the optimal development of individual potential. With this philosophical foundation, the Independent Curriculum is expected to produce a generation of Pancasila students who are creative, independent, have character, and are ready to face global challenges. Keywords: Philosophy of Education, Constructivism, Independent Curriculum, Progressivism